Value Criteria - Polušinas, Genadijus (Problemos, 1975)
In the article the author surveys the existing viewpoints on the category of value and brings forth his own solution of the problem by attempting to make the existing definitions more exact. Besides the author tries to establish the difference between value relation and value as a property of this relation. Peculiar attention is paid to stating and solving the question of the subjective criteria of value and the objective criterion of historical necessity.